Effect of Irrigation Fluid Temperature on Recurrence in the Evacuation of Chronic Subdural Hematoma - Andreas Bartley; Jiří Bártek; Asgeir Store Jakola; Jimmy Sundblom; Marie Fält; Petter Förander; Niklas Marklund; Magnus Tisell (2022)
The effect of a physical property of irrigation fluid (at body vs room temperature) on recurrence rate in the evacuation of chronic subdural hematoma (cSDH) needs further study.To explore whether irrigation fluid temperature has an influence on cSDH recurrence.This was a multicenter randomized clinical trial performed between March 16, 2016, and May 30, 2020. The follow-up period was 6 months. The study was conducted at 3 neurosurgical departments in Sweden. All patients older than 18 years undergoing cSDH evacuation during the study period were screened for eligibility in the study.The study participants were randomly assigned by 1:1 block randomization to the cSDH evacuation procedure with irrigation fluid at room temperature (RT group) or at body temperature (BT group).The primary end point was recurrence requiring reoperation within 6 months. Secondary end points were mortality, health-related quality of life, and complication frequency.At 6 months after surgery, 541 patients (mean [SD] age, 75.8 [9.8] years; 395 men [73%]) had a complete follow-up according to protocol. There were 39 of 277 recurrences (14%) requiring reoperation in the RT group, compared with 16 of 264 recurrences (6%) in the BT group (odds ratio, 2.56; 95% CI, 1.38-4.66; P < .001). There were no significant differences in mortality, health-related quality of life, or complication frequency.In this study, irrigation at body temperature was superior to irrigation at room temperature in terms of fewer recurrences. This is a simple, safe, and readily available technique to optimize outcome in patients with cSDH. When irrigation is used in cSDH surgery, irrigation fluid at body temperature should be considered standard of care.ClincalTrials.gov Identifier: NCT02757235.